2003
DOI: 10.1080/000164580310001105
|View full text |Cite
|
Sign up to set email alerts
|

Bone-anchored Hearing Aids in Unilateral Inner Ear Deafness

Abstract: In nine patients with unilateral deafness and normal hearing in the contralateral ear, measurements of sound localization and speech perception were obtained before intervention, with a conventional contralateral routing of sound (CROS) hearing aid and later with a bone-anchored hearing aid (BAHA) implanted in the deaf ear. Sound localization did not show any differences between the three conditions. Speech perception using short, everyday sentences showed a reduction in the head-shadow effect of 2 dB for both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
128
4
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(148 citation statements)
references
References 7 publications
14
128
4
2
Order By: Relevance
“…Previous free-field localization studies have also shown substantial localization deficits for listeners with a unilateral hearing loss (Angel and Fite, 1901;Jongkees and Van der Veer, 1957;Viehweg and Campbell, 1960;Gatehouse and Cox, 1972;Gatehouse, 1976;Humes et al, 1980;Newton and Hickson, 1981;Newton, 1983;Slattery and Middlebrooks, 1994;Bosman et al, 2003). Some of these studies reported near-normal localization performance in these monaural listeners (Newton, 1983;Slattery and Middlebrooks, 1994), a finding that is not supported by our results (Fig.…”
Section: Discussioncontrasting
confidence: 56%
“…Previous free-field localization studies have also shown substantial localization deficits for listeners with a unilateral hearing loss (Angel and Fite, 1901;Jongkees and Van der Veer, 1957;Viehweg and Campbell, 1960;Gatehouse and Cox, 1972;Gatehouse, 1976;Humes et al, 1980;Newton and Hickson, 1981;Newton, 1983;Slattery and Middlebrooks, 1994;Bosman et al, 2003). Some of these studies reported near-normal localization performance in these monaural listeners (Newton, 1983;Slattery and Middlebrooks, 1994), a finding that is not supported by our results (Fig.…”
Section: Discussioncontrasting
confidence: 56%
“…Results in 9 Nijmegen patients with one normal ear and one deaf ear, fitted with a transcranial BAHA CROS, support this assumption [Bosman et al, 2003]. More data on this appealing application will follow soon.…”
Section: The Baha In Patients With Unilateral Air-bone Gapsupporting
confidence: 53%
“…In particular speech intelligibility in noise and sound localization improved. In addition, a few authors found that the BAHA CROS was beneficial in specific listening situations, because some of the disadvantages of conventional CROS devices were avoided [Niparko et al, 2003;Bosman et al, 2003]. Obviously, the BAHA CROS is not capable of restoring binaural hearing in patients with unilateral profound hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, the BAHA CROS is not capable of restoring binaural hearing in patients with unilateral profound hearing loss. Nevertheless, these patients' opinions on the BAHA CROS are quite favorable, despite the small differences in measurement results between the aided and unaided conditions [Bosman et al, 2003]. To gain greater insight into the experience and opinions of patients with unilateral inner ear deafness we extended our group of unilateral inner ear deafness patients to 21 individuals.…”
Section: Introductionmentioning
confidence: 99%